Identification of the key material degradation mechanisms affecting silicon solar cells: Systematic literature review - Eshetu Tadesse Ymer; Hirpa Gelgele Lemu; Mesay Alemu Tolcha (Results in Engineering, 2025)
This literature review systematically identifies the primary material degradation mechanisms impacting silicon-based solar cells, which constitute over 90% of the global photovoltaic (PV) market. The study addresses the critical challenge of reduced solar cell performance and lifespan, driven by environmental and operational stressors, which subsequently diminish the efficiency and economic viability of solar energy systems. Employing a rigorous methodology structured on the PRISMA framework, we analyzed 181 peer-reviewed articles published between 2015 and 2024 to comprehensively evaluate various degradation pathways. Findings highlight that the degradation rate of silicon solar cells is highly sensitive to geographical location and climatic factors. Environmental elements are identified as major contributors to power output degradation, with observed annual losses ranging from 1.8% to 2% in hot-humid regions, notably higher than the approximately 0.3% reported in temperate zones. Specific degradation mechanisms include Potential-Induced Degradation, which can cause up to 30% efficiency loss by reducing short-circuit current density and open-circuit voltage, and Light-Induced Degradation, contributing up to 10% efficiency reduction. Dust accumulation is also a critical contributor to performance degradation, causing an average power loss of 1.27% per g/m2 and potentially leading to further issues such as encapsulant discoloration, corrosion of electrical contacts, and the development of thermal hotspots. Furthermore, surface-related degradation is influenced by factors such as emitter doping profiles, thermal oxide layers, and substrate materials. The study also examines the effects of thermal cycling and mechanical stress on silicon solar cells, demonstrating their ability to induce thermo-mechanical stress, resulting in various failure modes including solder joint disconnection, finger breakage, and cell fracture. Overall, the analyzed literature indicates annual degradation rates for silicon solar cells ranging from 0.25% to 3.3%. In conclusion, this review underscores the necessity of climate-specific module designs and tailored maintenance strategies, such as the implementation of PID-resistant cells and anti-soiling coatings, to significantly enhance PV durability. This work distinguishes itself from prior efforts by offering a comprehensive, quantitative synthesis of degradation mechanisms across diverse climatic conditions and technologies. It explicitly addresses existing gaps in long-term field data and the standardization of testing protocols, providing a more complete understanding crucial for advancing solar PV reliability.